Fatores relacionados com nível de atividade física em indivíduos amputados e a relação entre nível de atividade física com a qualidade de vida - Melo, Victor Hugo de (2014)
Physical activity has been recommended for its importance in the prevention of disease and health, although amputees have lower levels of physical activity, as well as changes in specific characteristics that may change the nature of the relationship between physical activity and quality of life. Therefore, the aim of this study was to investigate factors associated with higher levels of physical activity as well as to verify the relationship between physical activity and quality of life. For such a cross-sectional study using forms with social and clinical questionnaires and quality of life WHOQOL -BREF and the IPAQ physical activity questions was conducted. For categorical variables the chi-square test p < 0.05 was used, the numerical variables were evaluated using the Student t test p < 0.05 and variables with p < 0.2 were entered into a logistic regression model . The level of physical activity was correlated only with the physical and psychological domains p < 0.05 quality of life, and factors related to physical activity levels were age , functional independence and participation in the rehabilitation program p < 0 , 05. There was no change in the nature of the relationship between physical activity and quality of life , and rehabilitation program was the only variable associated with higher levels of physical activity , an increased risk of chance in twenty- five times for the individual to be active.